Examining the Role of Antisocial Personality Disorder in Intimate Partner Violence Among Substance Use Disorder Treatment Seekers With Clinically Significant Trauma Histories. (August 2015) - Dykstra, Rita E.; Schumacher, Julie A.; Mota, Natalie; Coffey, Scott F.
This study examined the associations among posttraumatic stress disorder (PTSD) symptom severity, antisocial personality disorder (ASPD) diagnosis, and intimate partner violence (IPV) in a sample of 145 substance abuse treatment-seeking men and women with positive trauma histories; sex was examined as a moderator. ASPD diagnosis significantly predicted both verbal and physical aggression; sex moderated the association between ASPD diagnosis and physical violence. PTSD symptom severity significantly predicted engaging in verbal, but not physical, aggression. Overall, these results suggest that an ASPD diagnosis may be an important risk factor for engaging in IPV among women seeking treatment for a substance use disorder.